Development of Handout with Magazine Display which Features by Concept Map about Interaction of Living Things and The Environment for Student of Class VII SMP - Sartika Fazlina; Ramadhan Sumarmin; Irma Leilani Eka Putri; Relsas Yogica (Bioeducation Journal, 2019)
Handout can be presented with a magazine display with concept maps. Pursuant to this matter done research with purpose to produce form handout with magazine display which have concept map about interaction of living creature and its environment of student class VII SMPN 12 Padang valid andpractical. This research is a research development conduted at FMIPA UNP and SMPN 12 Padang using model of development of Plomp 2013, that is initial investigation stage, development stage or prototype making and assessment phase. Handout validated by 3 lecturers department of Biology FMIPA UNP, 1 teacher Biology SMPN 12 Padang. Data in this research, data obtained from questionnaire of validity test and practice test. Data includes are primary data. The research produced a handout with magazine display with concept map about the interaction of living creatures and the environment for student of class VII SMP which is categorized with value 4,45 and stated very practical with 4,28 value by teacher and very practicalwith value 4,49 by learners.